Modeling the impacts of agricultural support policies on emissions from agriculture - Laborde Debucquet, David; Mamun, Abdullah; Martin, Will; Piñeiro, Valeria; Vos, Rob (International Food Policy Research Institute, 2020)
To understand the impacts of support programs on global emissions, this paper considers the impacts of domestic subsidies, price distortions at the border, and investments in emission-reducing technologies on global greenhouse gas (GHG) emissions from agriculture. In a step towards a full evaluation of the impacts, it uses a counterfactual global model scenario showing how much emissions from agricultural production would change if agricultural support were abolished worldwide. The analysis indicates that, without subsidies paid directly to farmers, output of some emission-intensive activities and agricultural emissions would be smaller. Without agricultural trade protection, however, emissions would be higher. This is partly because protection reduces global demand more than it increases global agricultural supply, and partly because some countries that currently tax agriculture have high emission intensities. Policies that directly reduce emission intensities yield much larger reductions in emissions than those that reduce emission intensities by increasing overall productivity because overall productivity growth creates a rebound effect by reducing product prices and expanding output. A key challenge is designing policy reforms that effectively reduce emissions without jeopardizing other key goals such as improving nutrition and reducing poverty. While the scenario analysis in this paper does not propose any particular policy reform, it does provide an important building block towards a full understanding the impacts of repurposed agricultural support measures on mitigation of greenhouse gas emissions and adaptation to climate change. That full analysis is being undertaken in subsequent work, which will also take account of land-use change and alternative forms of agricultural policy support to align objectives of food security, farmers’ income security, production efficiency and resilience, and environmental protection.